Damage simulation and strengthening of main girder after the fire-induced fracture of stay cables during construction. (November 2022) - Dai, Lizhao; Liu, Yaofeng; Liu, Guokun; Yan, Donghuang; Yuan, Ming; Wang, Lei
Abstract: The fire-induced fracture of stay cables damages the main girder of a cable-stayed bridge during the cantilever construction. A scaled-down girder was designed in the laboratory to simulate the mechanical behavior of the damaged main girder. A special loading system, consisting of external prestressing strands and two actuators, was designed to simulate the damage of the main girder. A strengthening strategy, consisting of anchor bolts and steel plates, was presented to improve the stiffness and flexural capacity of the damaged girder. The results showed that the special loading system and the strengthening strategy could effectively achieve their respective goals. After strengthening, the vertical and transverse bending stiffness and the positive and negative torsional stiffness of the girder increased by 42%, 31%, 78%, and 68%, respectively, from those of the damaged girder. The findings of the present study can provide an effective basis for the damaged simulation of main girder after the fire-induced fracture of stay cables and the selection of strengthened method for damaged main girder during the cantilever construction.